Development of elite adolescent golfers - Hayman, R.; Polman, R.; Taylor, J.; Hemmings, B.; Borkoles, E. (Talent Development & Excellence, 2011)
This study examined the nature of developmental, psychosocial and contextual factors experienced by elite adolescent golfers in an effort to establish which factors might be important to achieve elite status in golf. Participants were guided through a structured interview collecting quantitative data (after Cote, Ericsson & Law, 2005). Participants were eight Caucasian male adolescent amateur golfers with a handicap between +2 and +4. All were affiliated with international representative teams run by the English Golf Union. Participants did not follow an early specialisation trajectory and refrained from engagement within long term golf specific deliberate practice. Instead, participants encountered numerous sporting activities within a playful, developmentally supportive environment until selection for international representative teams during late adolescence, at which point deliberate practice became more evident. Such findings may provide practitioners within golf talent development systems with stronger scientific basis for their coaching and development interventions.